Determinants Of Halal Cosmetic Purchase Decisions Among Generation Y And Z Consumers: Evidence From Wardah Users Determinants Of Halal Cosmetic Purchase Decisions Among Generation Y And Z Consumers: Evidence From Wardah Users - Ihsan Mulia Siregar; Siti Ena Aisyah Simbolon; Tetti Maisyaroh; Maisarah Lubis; Sofa Marwah; Sri Fatimah Hasibuan; Siti Eni Aisyah Simbolon (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
The halal cosmetics industry in Indonesia has experienced rapid growth over the past decade, driven by increasing consumer awareness of halal products that emphasize not only religious compliance but also quality, safety, and ethical values. As one of the world’s largest consumers of halal products, Indonesia offers significant market potential, particularly in the cosmetics sector. Wardah, a local halal cosmetics brand, has successfully positioned itself as a market leader through continuous product innovation, strong brand awareness, and effective use of electronic word of mouth (e-WOM). This study aims to analyze the influence of product innovation, brand awareness, and e-WOM on consumers’ purchasing decisions for Wardah products. A quantitative research approach was employed using a Likert-scale questionnaire distributed to 245 Generation Y and Generation Z Wardah users in South Tapanuli. The collected data were analyzed using Partial Least Square (PLS) with SmartPLS 3.0. The results indicate that product innovation, brand awareness, and e-WOM have a positive and significant effect on purchasing decisions. The R-square value of 0.777 demonstrates that these three variables explain 77.7% of the variance in purchasing decisions, with e-WOM showing the strongest influence among the variables. These findings highlight the importance of continuous product innovation, strengthening brand awareness, and leveraging online reviews and digital communities to enhance consumer trust and purchase intention. This study provides empirical insights that can support the development of effective marketing strategies for halal cosmetics in Indonesia.